The effect of residential house rent on Urban households poverty status in Ethiopia: evidence from Wolkite town - Endalkachew Kabtamu Mekonen (Cogent Economics & Finance)
The study investigated the effect of residential house rent on urban household poverty status in Ethiopia with evidence from Wolkite town. By using structured questionnaires, primary data was collected from 248 household heads living in rental housing. In addition, a key-informant interview was conducted with the town municipality offices for triangulation purposes. The collected data were analysed by using descriptive and inferential statistic. The inferential statistic was estimated by using logistic regression model. The statistical package used to estimate the model was STATA version 14. The empirical result shows that rising residential house rent increases the poverty status of urban households. The poverty status of households is also negatively associated with access to housing allowance. Policy makers should note that the source and scope of poverty is varied. Poverty reduction policy should account the rental price of housing and integrate it with the broader national policies. Thus, the issue of residential house rent and housing should be part and parcel of the poverty reduction strategy of the government. Housing policies should also be integrated with other objectives of the government. A timely revised housing allowance and housing opportunities should be accessible to the low-income households.